Adult-Onset Hearing Impairment Induces Layer-Specific Cortical Reorganization: Evidence of Crossmodal Plasticity and Central Gain Enhancement - Schormans, Ashley L (Cereb Cortex, 2019)
Adult-onset hearing impairment can lead to hyperactivity in the auditory pathway (i.e., central gain enhancement) as well as increased cortical responsiveness to nonauditory stimuli (i.e., crossmodal plasticity). However, it remained unclear to what extent hearing loss-induced hyperactivity is relayed beyond the auditory cortex, and thus, whether central gain enhancement competes or coexists with crossmodal plasticity throughout the distinct layers of the audiovisual cortex. To that end, we investigated the effects of partial hearing loss on laminar processing in the auditory, visual and audiovisual cortices of adult rats using extracellular electrophysiological recordings performed 2 weeks after loud noise exposure. Current-source density analyses revealed that central gain enhancement was not relayed to the audiovisual cortex (V2L), and was instead restricted to the granular layer of the higher order auditory area, AuD. In contrast, crossmodal plasticity was evident across multiple cortical layers within V2L, and also manifested in AuD. Surprisingly, despite this coexistence of central gain enhancement and crossmodal plasticity, noise exposure did not disrupt the responsiveness of these neighboring cortical regions to combined audiovisual stimuli. Overall, we have shown for the first time that adult-onset hearing impairment causes a complex assortment of intramodal and crossmodal changes across the layers of higher order sensory cortices.